The Animal as Fourth Educator: A Literature Review of Animals and Young Children in Pedagogical Relationships. Issue 2 (June 2013) - Bone, Jane
THIS LITERATURE REVIEW PRESENTS the case for acknowledging the animal in early childhood settings as the fourth educator. This idea builds on the work of Malaguzzi (1998), who proposed the environment as third teacher. Drawing on a range of research as well as changing perspectives about the animal and child relationship, the literature presented here argues for the animal to be considered respectfully as a pedagogical support and motivator for learning. The review covers interdisciplinary aspects of the field of human and animal relationships and also draws on new work about animals in mechanical/robot form. These animal and machine intersections come together in posthuman theory. The review highlights opportunities for research in this increasingly important area.